Organizational Structure and Performance of Plant Turnaround Maintenance in Large Process-Based Industries in Malaysia: A Conceptual Framework - Ghazali, Zulkipli (2008)

(untitled)
Plant turnaround maintenance is a crucial asset management in technology intensive industries and normally practiced in large process-based industries. The highly competitive business environment has further raised its importance. A conceptual framework is proposed to systematically gain scientific knowledge on the organizational structure and performance of plant turnaround maintenance. This is a step towards filling the gap in the literature on plant turnaround maintenance. This paper discusses the linkages between plant technology, size, organizational structure, and performance of plant turnaround maintenance in large process-based industries in Malaysia. A conceptual model of relationships is developed for empirical analysis.